VISFATIN LEVEL DISTURBANCES IN PERIPHERAL BLOOD OF PATIENTS WITH DIABETIC NEPHROPATHY - Topchii, I.I.; Semenovykh, P.S.; Galchinskaya, V.YU.; Yefimova, N.V. (Ukrainian Journal of Nephrology and Dialysis, 2014)
Introduction. Recent studies suggest that visfatin participates in pathogenesis of vascular diabetic complications, in particular diabetic nephropathy (DN). The aim of the present research - definition of visfatin level in peripheral blood of type 2 diabetic patients taking to account renal function disturbances and body mass index (BMI). Materials and methods. 94 type 2 diabetic patients with different stages of DN and 10 healthy subjects (control group) were observed. Visfatin concentration in blood plasma was determined using immunoassay kit. Results. An essential increase of visfatin level in blood plasma took place already in initial stages of the DN. Progressing of the disease was accompanied by more expressed growth of visfatin concentration. In patients with high BMI substantial increase of visfatin level when compared with those with normal IMT was determined. We established strong correlations between visfatin concentrations, urinary albumin levels and blood creatinine concentrations and negative correlations with glomerular filtration rate. Conclusions: Our findings testify that visfatin level displays a functional kidney state and may be used as addition to traditional methods of patients examination.